The English language in the Malaysian education system - Anna Lynn Abu Bakar; Mohd. Sohaimi Esa; Romzi Ationg; Esther Jawing (Global Academic Excellence, 2021)
The purpose of this article is to provide a historical account of the English language in Malaysia. Malaysians' linguistic and educational backgrounds are intricately linked to the country's historical and educational traditions. Despite the evolution of the Malaysian educational system, the English language continues to be taught as a compulsory language in schools. It is a method of engaging students in interaction and meaningful communication that is known as communicative language teaching. Language learners who are still required to learn English in universities must cultivate a positive attitude in order to engage in meaningful learning activities.